Diversification in the international construction business. Issue 6 (3rd June 2018) - Ye, Meng; Lu, Weisheng; Flanagan, Roger; Ye, Kunhui
Abstract: Economic globalization has created an interdependent market that allows companies to transcend traditional national boundaries to conduct business overseas. In the international construction market, companies often adopt diversification as a strategy for growth, for risk management or for both. However, the diversification patterns of international construction companies (ICCs) as a group are barely clear. The primary aim of this research is to cover this knowledge void by mapping ICCs' diversification patterns in both business sectors and geographical dispersal. It starts from a literature review of diversification theories. Based on the review, a series of hypotheses relating to ICCs' diversification are proposed. Data are gleaned from Engineering News - Record, i.e. Bloomberg and Capital IQ, ranging from 2001 to 2015. By testing the hypotheses, it is found that larger ICCs prefer to diversify than their smaller counterparts. Most of the ICCs tend to diversify to geographical markets with similar cultural or institutional environment. Market demands drive ICCs to diversify to different geographical markets while they are more prudential in venturing into new business sectors. The research provides not only valuable insights into diversification patterns of ICCs, but also a solid point of departure for future theoretical and empirical studies.